Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1002/1098-2280(2001)37:1<31::aid-em1004>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

HUman MicroNucleus project: international database comparison for results with the cytokinesis‐block micronucleus assay in human lymphocytes: I. Effect of laboratory protocol, scoring criteria, and host factors on the frequency of micronuclei

Abstract: Micronucleus (MN) expression in peripheral blood lymphocytes is well established as a standard method for monitoring chromosome damage in human populations. The first results of an analysis of pooled data from laboratories using the cytokinesis-block micronucleus (CBMN) assay and participating in the HUMN (HUman MicroNucleus project) international collaborative study are presented. The effects of laboratory protocol, scoring criteria, and host factors on baseline micronucleated binucleate cell (MNC) frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
45
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 0 publications
11
45
1
2
Order By: Relevance
“…Significant associations were found between age and cytogenetic parameters where age had an influence on the MN frequency of tannery workers. MN frequency has been found to be higher in females (Bonassi et al 2001), while gender differences in comet assay is still a matter of discussion (Heuser et al 2002;Moller 2006). The influence of age in comet assay results are also controversial and still under discussion (Silva et al 2000;Heuser et al 2002Heuser et al , 2007Moller 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Significant associations were found between age and cytogenetic parameters where age had an influence on the MN frequency of tannery workers. MN frequency has been found to be higher in females (Bonassi et al 2001), while gender differences in comet assay is still a matter of discussion (Heuser et al 2002;Moller 2006). The influence of age in comet assay results are also controversial and still under discussion (Silva et al 2000;Heuser et al 2002Heuser et al , 2007Moller 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Even the frequencies in the exposed population were much lower than what is normally reported in unexposed control cells. Bonassi et al (2001), for example, reported an overall median micronucleus frequency in non-exposed (i.e. normal) subjects of 6.5 per thousand and an interquartile range between 3 and 12 per thousand.…”
Section: Discussionmentioning
confidence: 58%
“…This variability together with inconsistent study design is a major reason why the MNT has been almost neglected in the field of breast cancer research despite the fact that almost all published studies revealed significant differences. The test variation is considerable and influenced by type of culture medium, storage time of blood before starting the culture [5], and the persons carrying out visual counting [17]. To overcome these problems, standardization of cell cultures and analysis of confounding factors, as done by the HUMN (HUman MicronNucleus) project [9], have been proposed.…”
Section: Discussionmentioning
confidence: 99%